Addressing the security challenges of using containers. Issue 12 (December 2016) - Pittenger, Mike
Abstract : Containers have taken the open source ecosystem by storm, providing a fast and effective way to deliver and deploy a compact, portable environment for running applications across shared server resources. Container technology is another breakthrough in the constant drive to increase development agility and get products to market more quickly. Speed and agility are key drivers for container adoption in the enterprise, but those drivers can't be at the expense of security. Enterprises need to take realistic precautions before completely embracing this approach to operating-system-level virtualisation. Containers have taken the open source ecosystem by storm, providing a fast and effective way to deliver and deploy a compact, portable environment for running applications across shared server resources. Container technology is another breakthrough in the constant drive to increase development agility and get products to market more quickly. But that can't be at the expense of security. Enterprises need to take realistic precautions before completely embracing this approach to operating system-level virtualisation, explains Mike Pittenger of Black Duck Software.